2021
DOI: 10.1002/er.7212
|View full text |Cite
|
Sign up to set email alerts
|

A novel calcium looping–integrated NGCC power plant configuration for carbon capture and utilization—Comprehensive performance analysis

Abstract: Energy plays a pivotal role in industrial development of any country. At present, most of the countries are utilizing fossil fuels, mainly coal and natural gas as energy sources for power production. However, these sources emit high amounts of carbon dioxide (CO 2 ) into the atmosphere resulting in global warming. Hence, the fossil fuel-based thermal power plants need to be integrated with CO 2 sequestration and utilization processes for sustainable power production. In this work, four natural gas combined cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…This paragraph deals with the exergy analysis of separation processes ("stand alone") as it is appearing in an increasing number of works [18][19][20][24][25][26][27] mostly for the postcombustion scheme.…”
Section: Exergy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This paragraph deals with the exergy analysis of separation processes ("stand alone") as it is appearing in an increasing number of works [18][19][20][24][25][26][27] mostly for the postcombustion scheme.…”
Section: Exergy Analysismentioning
confidence: 99%
“…Some alternative innovations under development are ion transport membranes (ITMs) and oxyfuel combustion with internally generated oxygen and chemical looping combustion. [23][24][25] Current values of energy consumption are around 130 kWh/t O2 for ASU that consists of the cryogenic distillation of gases with different volatilities. 38,[42][43][44] From the point of view of the "exergy analysis," we will focus on the simulation of the air separation unit, as represented in the simplified scheme of Figure 13 described by several papers.…”
Section: Exergy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Such a layout resulted in a net efficiency penalty of 0.1% points (without CO2 compression) and 4% points (with CO2 compression). Moreover, Pillai et al [16] demonstrated that the CaL retrofit to a natural gas combined cycle plant and dimethyl ether production would result in an efficiency penalty of 8.2% points and a CO2 avoided cost of 15 €/tCO2. As a result of superior thermodynamic performance, a CO2 avoided cost for the CaL retrofits was demonstrated to fall between 10-30 €/tCO2 [14].…”
Section: Introductionmentioning
confidence: 99%
“…hydrogen production [11], and synthesis of chemicals, such as dimethyl ether [16] and synthetic natural gas [20].…”
Section: Introductionmentioning
confidence: 99%